A Pedagogia da alternância na visão dos egressos da EFA de Porto Nacional - TO: a possibilidade de uma formação integral - CAVALCANTE, Nilton Vale (2009)
In this study it was analized how the Integral Formation of young people, one of the main purposes of the network Centros Familiares de Formação por Alternância (Familiar Centers of Alternation Formation), has been happening at Escola Família Agrícola (Agricultural Family School), in the city of Porto Nacional, and how occurs the participation of its egresses in the different aspects of social life. The research is based on the qualitative approach with dialectical perpective, that here has the form of case study. We combined the use of bibliographic research with other methodological procedures, such as documentary research from which it was analysed, among other situations, the Political and Pedagogical Project of the Agricultural Family School, reports, Education Laws and opinions. We still applied semistructuralized type interviews, with 14 chosen egresses, after applying a questionnaire answered by 32 of the 103 total students that had finished the High School and Professional Education at the Agricultural Family School, until the year of 2006. At the main documents of that School, it was clear the assumption that it can contribute with the Integral Formation of its young people, by trainning them for the citizenship and building a culture of participation. The Country Education, in Brazil history, is a concrete example of indifference and refuse of a right by the Brazilian State, from what is responsability of public policies to include the country population. It is in this empty of denying people their rigths, not only done by the State, but also and mainly by the powerful social elites of Brazil, that it is born, within the civil society of Porto Nacional, the Agricultural Family School, helping country people of that region. The Agricultural Family School was created by COMSAÚDE, a nongovernmental organization, and it came from debates with country comunities of Porto Nacional and local Social Movements. One of the purposes to the creation of the School is to help people that live at the country region, giving them a quality education and reflecting the particularities of that population, working with the Familiar Agriculture. The research concluded that the Scool advances by working knowledge from reading people reality, in the light of other knowledges and possibilities and that the School contributes to form citizens at the Integral Formation of its young people.